Establishing a mouse model of lung metastases using ultrasound-guided right heart ventricle injection - Amanda Labora; Amanda Creech; Hailey Lee; Erin Tabornal; Caius Radu; Timothy Donahue (STAR Protocols, 2023)
Summary: We report a technique to generate a murine model of lung metastases by selectively injecting tumor cells into the right heart ventricle under ultrasound guidance. First, we describe cell preparation and reference animal preparation as previously described. We then detail the technique using a previously described 3D-printed instrument stabilization device. Finally, we describe tumor growth surveillance using bioluminescent imaging.For complete details on the use and execution of this protocol, please refer to Labora et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.